Pengaruh Promosi dan Harga Terhadap Keputusan Pembelian Pada Pelanggan Makaroni Ngehe Kediri - Octarini, Adinda Puspa; Ruhamak, Muhammad Dian; Andarini, Marwita (Universitas Kadiri, 2023)
This study aims to determine the effect of price and Promotion on Macaroni Ngehe Kediri's purchasing decisions. The research sample is 100 respondents who are customers of Makaroni Ngehe Kediri. Data was collected by distributing questionnaires and processing this data using SPSS. The research model used is a descriptive research model that systematically and accurately describes the factors studied. The data testing technique used in this research is to test the validity with the value of r count and the reliability with Cronbach's Alpha; the data analysis used is multiple linear regression analysis to test and prove the research hypothesis. The constant value is 0.029; for Promotion, it is 0.475, and the price value is 0.620, so the multiple linear regression equations Y = -0.029 + 0.475 (X2) +0.620 (X2) can be obtained. Promotion and price together affect consumer purchasing decMacaronit Macaroni Ng; itKediri, it can be seen that the significance value for the effect of Promotion and price is 0.000 <0.05 and the calculated f value is 222.059 > the f table value is 3.15. So, it can be concluded that Promotion and Price influence the purchasing decision variable.